2021
DOI: 10.1146/annurev-economics-083120-111540
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Risk in Financial Networks: A Survey

Abstract: We provide an overview of the relationship between financial networks and systemic risk. We present a taxonomy of different types of systemic risk, differentiating between direct externalities between financial organizations (e.g., defaults, correlated portfolios, fire sales), and perceptions and feedback effects (e.g., bank runs, credit freezes). We also discuss optimal regulation and bailouts, measurements of systemic risk and financial centrality, choices by banks regarding their portfolios and partnerships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 141 publications
0
31
0
Order By: Relevance
“…Rich and in-depth investigations into these events have demonstrated that the risks not only influence each individual entity in the system but also spread among the entities and evolve into system-wide crises. In other words, the entities in a financial market are interdependent on each other, forming a complex networked system that enables the contagion of risks through the interdependencies [4][5][6]. Financial systems are thus normally modeled as networks, such as the networks of financial institutions [7,8], the network of stock indices [9], and the network of commodity futures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rich and in-depth investigations into these events have demonstrated that the risks not only influence each individual entity in the system but also spread among the entities and evolve into system-wide crises. In other words, the entities in a financial market are interdependent on each other, forming a complex networked system that enables the contagion of risks through the interdependencies [4][5][6]. Financial systems are thus normally modeled as networks, such as the networks of financial institutions [7,8], the network of stock indices [9], and the network of commodity futures [10].…”
Section: Introductionmentioning
confidence: 99%
“…An agent's initial endowment includes all the agent's tangible and intangible assets but excludes the claims and liabilities the agent has towards the other agents. For outstanding surveys of this literature, we refer the reader to Glasserman and Young (2016) and Jackson and Pernoud (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed while these links allows banks to cope with liquidity fluctuations and transfer risk, they can also become channels through which distress can spread, turning an idiosyncratic shock into a systemic one. Solvency contagion played a major role in the Global Financial Crisis of 2007/08 [25] and thus received large attention from the literature (we remand the reader to recent reviews [26][27][28]). A general dynamical model for solvency contagion is represented by the DebtRank algorithm [29][30][31], which describes the following situation.…”
Section: Introductionmentioning
confidence: 99%